Triacylglycerol and phytyl ester synthesis in Synechocystis sp. PCC6803 - Aizouq, Mohammed (Proc Natl Acad Sci U S A, 2020)
Cyanobacteria are unicellular prokaryotic algae that perform oxygenic photosynthesis, similar to plants. The cells harbor thylakoid membranes composed of lipids related to those of chloroplasts in plants to accommodate the complexes of photosynthesis. The occurrence of storage lipids, including triacylglycerol or wax esters, which are found in plants, animals, and some bacteria, nevertheless remained unclear in cyanobacteria. We show here that the cyanobacterium Synechocystis sp. PCC6803 accumulates both triacylglycerol and wax esters (fatty acid phytyl esters). Phytyl esters accumulate in higher levels under abiotic stress conditions. The analysis of an insertional mutant revealed that the acyltransferase slr2103, with sequence similarity to plant esterase/lipase/thioesterase (ELT) proteins, is essential for triacylglycerol and phytyl ester synthesis in Synechocystis. The recombinant slr2103 enzyme showed acyltransferase activity with phytol and diacylglycerol, thus producing phytyl esters and triacylglycerol. Acyl-CoA thioesters were the preferred acyl donors, while acyl-ACP (acyl carrier protein), free fatty acids, or galactolipid-bound fatty acids were poor substrates. The slr2103 protein sequence is unrelated to acyltransferases from bacteria (AtfA) or plants (DGAT1, DGAT2, PDAT), and therefore establishes an independent group of bacterial acyltransferases involved in triacylglycerol and wax ester synthesis. The identification of the gene slr2103 responsible for triacylglycerol synthesis in cyanobacteria opens the possibility of using prokaryotic photosynthetic cells in biotechnological applications.